The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1074/jbc.m110.167718
|View full text |Cite
|
Sign up to set email alerts
|

Losac, the First Hemolin that Exhibits Procogulant Activity through Selective Factor X Proteolytic Activation

Abstract: Envenoming by the contact of human skin with Lonomia obliqua caterpillars promotes a hemorrhagic syndrome characterized by a consumptive coagulopathy. Losac (Lonomia obliqua Stuart factor activator) is a component of the bristle of L. obliqua that is probably partially responsible for the observed syndrome because it activates factor X and is recognized by an effective antilonomic serum. Here we unveil the proteolytic activity of Losac and demonstrate the feasibility of its recombinant production. On the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 62 publications
2
38
0
Order By: Relevance
“…Some years later, from a cDNA library of L. obliqua bristle transcripts [19], the specific clone encoding for Losac was identified and the recombinant protein produced in bacteria system (for details, see section 3.3). Studies using the native or recombinant form of Losac (rLosac) revealed specificity toward factor X [20,22,28]. Moreover, Losac had no effect on fibrin or fibrinogen, indicating its specificity for blood coagulation activation, and it was recognized by the antilonomic serum produced in Butantan Institute.…”
Section: Losac: Functional Characterizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Some years later, from a cDNA library of L. obliqua bristle transcripts [19], the specific clone encoding for Losac was identified and the recombinant protein produced in bacteria system (for details, see section 3.3). Studies using the native or recombinant form of Losac (rLosac) revealed specificity toward factor X [20,22,28]. Moreover, Losac had no effect on fibrin or fibrinogen, indicating its specificity for blood coagulation activation, and it was recognized by the antilonomic serum produced in Butantan Institute.…”
Section: Losac: Functional Characterizationmentioning
confidence: 99%
“…Although there are strong functional similarities, the major difference is in the structure of both activators. Apparently, Losac activates factor X through a serine protease-like activity, while RVV-X has a typical metalloproteinase structure [20,28,84].…”
Section: Losac: Functional Characterizationmentioning
confidence: 99%
See 3 more Smart Citations